The Influence Of Debt To Assets Ratio And Return On Equity On Stock Prices At PT Ristia Bintang Mahkotasejati TBK For The 2013-2023 Period - Adelia, Meirizka; Khoiriah, Neneng (Jurnal Multidisiplin Sahombu, 2025)
This study aims to determine the effect of the Debt to Assets Ratio (DAR) and Return on Equity (ROE) on the Share Price of PT Ristia Bintang Mahkotasejati Tbk for the period under review. A quantitative descriptive method is used in this research. The results of the partial t-test analysis indicate that DAR does not significantly affect the Share Price, as the significance value exceeds the threshold, and the calculated t-value is below the critical value. Conversely, ROE has a significant partial effect on the Share Price, as evidenced by a significance value below the threshold and a calculated t-value exceeding the critical value. The simultaneous test results show that DAR and ROE together have a significant effect on the Share Price, supported by a significance value below the acceptable threshold and a calculated F-value exceeding the critical value. The coefficient of determination indicates that the combined influence of DAR and ROE explains approximately half of the variability in the Share Price, while the remaining portion is influenced by other variables not included in the study. This highlights the importance of these financial ratios in determining stock performance while acknowledging the impact of external factors.